2011
DOI: 10.1186/1471-2407-11-351
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-associated down-regulation of RASSF1A and up-regulation of RASSF1Cin pancreatic endocrine tumors

Abstract: BackgroundRASSF1A gene silencing by DNA methylation has been suggested as a major event in pancreatic endocrine tumor (PET) but RASSF1A expression has never been studied. The RASSF1 locus contains two CpG islands (A and C) and generates seven transcripts (RASSF1A-RASSF1G) by differential promoter usage and alternative splicing.MethodsWe studied 20 primary PETs, their matched normal pancreas and three PET cell lines for the (i) methylation status of the RASSF1 CpG islands using methylation-specific PCR and pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 31 publications
4
68
0
1
Order By: Relevance
“…Pyrosequencing revealed high variability of a distribution and level of RASSF1A promoter methylation within and among pancreatic cancer samples [129]. The same variability was shown ten years earlier in breast cancer using an oligonucleotide-based microarray technique [130].…”
Section: Epigenetic Regulation Of the Rassfsmentioning
confidence: 90%
“…Pyrosequencing revealed high variability of a distribution and level of RASSF1A promoter methylation within and among pancreatic cancer samples [129]. The same variability was shown ten years earlier in breast cancer using an oligonucleotide-based microarray technique [130].…”
Section: Epigenetic Regulation Of the Rassfsmentioning
confidence: 90%
“…Several studies indicated RASSF1A as one of the most hypermethylated genes in PanNET and more frequently in metastatic tumours compared to nonmetastatic ones. Interestingly, RASSF1A promoter was found methylated in normal pancreas as well, although to a lower level (Dammann et al 2003, Malpeli et al 2011. We found VHL promoter (VHL-associated gene) hyper-methylation in a subset of PanNET in correlation with intra-tumoural hypoxia and poor prognosis (Schmitt et al 2009).…”
Section: Pancreatic Netmentioning
confidence: 98%
“…Separate studies have identified RASSF1 promoter methylation in 80-83% of pNETs making it the most frequently altered gene in sporadic pNET identified to date. In some cases, methylation is also identified in matched normal pancreas, however at a lower level of expression (Dammann et al 2003a, Malpeli et al 2011. RASSF1 methylation has been noted to be more frequent in metastatic tumours (100%) than non-metastatic (71%) (Malpeli et al 2011).…”
Section: Dna Methylation In Pnetmentioning
confidence: 97%
“…In contrast to RASSF1A, the RASSF1C isoform expression is 11.4 times higher in pNET than in normal tissue (PZ0.001) (Malpeli et al 2011). RASSF1C has been shown to have a role inhibiting b-catenin degradation and given the above findings may also have a pathogenic role in pNET development (Estrabaud et al 2007).…”
Section: Dna Methylation In Pnetmentioning
confidence: 99%
See 1 more Smart Citation